Determination of Young’s Modulus by Specific Vibration of Basalt and Diabase - Osvail André Quaglio; José Margarida da Silva; Edmo da Cunha Rodovalho; Leandro de Vilhena Costa (Advances in Materials Science and Engineering)
The elasticity is an important parameter for the evaluation of the mechanical behavior of a rock mass and a fundamental factor in the definition of the resistance characteristics, stability, and blastability in rock blasts, and it is an important parameter for the blastability equations like the Kuz–Ram method. This paper presents a comparison of the Uniaxial Compression Method (UCM) and the Impulse Excitation Technique (IET) in determining Young’s modulus. The IET is a static and nondestructive dynamic method of characterizing mechanical parameters of materials, while the UCM is a quasistatic and destructive method. We determined Young’s modulus of samples from nine basalt and diabase mines used as aggregates in the construction industry. Young’s modulus was determined by the acoustic response due to longitudinal oscillations caused by a mechanical impulse (IET) in the Sonelastic equipment and the stress-strain curve (UCM). Young’s modulus values showed high repeatability and agreed with those reported in the literature for the same material. The work shows that the solnelastic is an innovate equipment and elucidated advantages of IET in comparison to the UCM such as shorter execution time, greater safety, and a lower cost ranging from 11.5% to 22.5% of the UCM.